Anti-aging high-stability full-shading film and preparation method thereof
By cross-linking reaction of modified polyurethane and epoxy resin, and adding PBT and specific light-shielding fillers, the problems of aging and insufficient weather resistance of the full light-shielding film are solved, and a full light-shielding film with high stability and long-term light-shielding effect is achieved.
Patent Information
- Application Number
- CN202411711665.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-26
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
The existing full-blocking films are prone to aging during use, and lack weather resistance and long-term light-shielding properties, making it difficult to meet market demand.
The cross-linking reaction of modified polyurethane and epoxy resin is used to form a cross-linking framework, and polybutylene terephthalate PBT is added to improve the toughness and durability of the material. At the same time, activated carbon-loaded nanotitanium dioxide, carbon black and chromium black powder are used as light shielding fillers, and light reflection aids and antioxidants are combined to optimize the light shielding and reflection effects.
It significantly improves the aging resistance and weather resistance of the full light-shielding film, extends the service life, ensures the uniformity and efficiency of the light-shielding effect, and reduces manufacturing costs.
Smart Images

Figure BDA0005155900660000111 
Figure BDA0005155900660000121
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of shading materials, and specifically relates to an aging-resistant and highly stable full shading film and a preparation method thereof. Background Art
[0002] At present, the common shading layers of curtain roller blinds on the market mainly include coated fabrics and shading fabrics. Coated fabrics are coated on the selected fabrics by coating equipment, and need to be brushed 2-3 times to achieve the desired functional effect. Moreover, the coating slurry on the fabric contains harmful solvents such as benzene series to make the coating surface smooth and flat. The coating slurry is sometimes synthesized from a variety of chemical raw materials. The coating process will produce more waste gas and wastewater, and the coating process is complicated. It is not in line with the current environmental protection trend. In addition, the curtain roller blinds using coated fabrics are prone to aging, falling off, and are not resistant to washing and dry cleaning, which is not conducive to later cleaning and affects the appearance. Woven fabrics are woven by jacquard machines, using a bottom layer of fabric, a surface layer, and a row of black shading silk in the middle. The fabric has a high gram weight, a heavy gram weight, and it is difficult to achieve complete shading in terms of function. Therefore, the use of shading film and ordinary textiles to bond to prepare shading curtains has gradually become the mainstream process for the preparation of shading curtains.
[0003] However, since the sunshade film needs to block light for a long time, the full sunshade film absorbs heat significantly during use, and the black sunshade film is easily aged due to heat absorption, which reduces the service life of the sunshade film. In addition, the large amount of inorganic pigments added for sunshade effect increases the rigidity of the sunshade film and reduces its weather resistance, making the stability of these products poor. After a period of use, its sunshade and sun protection effect deteriorates rapidly, making it difficult to meet the needs of the existing consumer market. How to simultaneously improve the weather resistance and long-term sunshade properties of the sunshade film is an important issue that needs to be urgently solved in the current sunshade film application field. Summary of the invention
[0004] In view of the problem that the existing full light-shielding films have insufficient weather resistance and long-term light-shielding properties, the present application provides an aging-resistant and highly stable full light-shielding film and a preparation method thereof.
[0005] In the first aspect, the present application provides an aging-resistant and highly stable full-light-shielding film, comprising the following components calculated in parts by weight: 38-50 parts of modified polyurethane TPU, 10-15 parts of PBT, 15-18 parts of epoxy resin, 5-8 parts of lubricant, 8-16 parts of light-shielding filler, 3-5 parts of light-reflecting agent, and 1-1.5 parts of antioxidant.
[0006] By adopting the above technical scheme, a cross-linked skeleton is provided by cross-linking reaction of modified polyurethane and epoxy resin, and epoxy resin exhibits excellent physical properties and chemical corrosion resistance on the above structural frame, forming the basis of a flexible and durable full light-shielding film material, and then by adding polybutylene terephthalate PBT, which belongs to the polyester series, the longer ester chain segment in the crystalline thermoplastic polyester resin can be deeply wound on the above structural frame, further improving the toughness and wear resistance of the overall material, improving the structural strength, drape and durability of the full light-shielding film, and the light-shielding filler can effectively block the light, and the light-shielding effect is good. The mixed use of the light-shielding filler and the light-reflecting additive can give full play to the light-shielding and light-reflecting effects, avoid direct light exposure to the dark light-shielding layer and accelerate the aging of the dark light-shielding layer, and extend the service life of the whole full light-shielding film. The overall color deviation of the product made in this way is small, and the light-shielding effect of the product is uniform and consistent. It can be used to make full light-shielding curtains, roller blinds, tents, sunshade cloths, etc., with a wide range of uses, reducing manufacturing costs and increasing the demand for high-quality products.
[0007] In a specific embodiment, the modified polyurethane TPU is an acrylic modified polyurethane TPU, and the preparation method includes the following steps: mixing and reacting a diol with an isocyanate to obtain a prepolymer terminated with isocyanate groups at both ends; and then mixing and reacting with a hydroxyl-containing acrylate to obtain the acrylic modified polyurethane TPU.
[0008] By adopting the above technical solution, the double bonds on the acrylic functional groups in the modified polyurethane TPU undergo addition reaction with the epoxy groups to form a stable cross-linking structure.
[0009] The light-shielding filler comprises activated carbon-loaded nano titanium dioxide, carbon black and chrome black powder.
[0010] By adopting the above technical solution, activated carbon-loaded nano-titanium dioxide is combined with two shading fillers. The activated carbon-loaded nano-titanium dioxide has the function of reflecting light, which can produce good reflection and scattering, and prevent light from passing through the composite material. The full shading film has certain mechanical properties, while the aging resistance and weather resistance are significantly improved. Under the premise of ensuring the shading rate, the weather resistance is greatly improved.
[0011] In a specific embodiment, the preparation method of the activated carbon-supported nano-titanium dioxide comprises mixing and adsorbing activated carbon and an ethanol solution of tetrabutyl titanate, and standing for 1-2 hours to obtain a precursor; the precursor is dried and calcined to obtain the activated carbon-supported nano-titanium dioxide.
[0012] By loading nano-titanium dioxide on activated carbon, on the one hand, the light-shielding property of the material is ensured, and titanium dioxide agglomeration is avoided, the dispersion of the material is improved, the light-shielding property is uniform, and the anti-aging performance of the material is improved; the embeddedness and bonding strength of nano-titanium dioxide and the structural frame are ensured, and the uneven light-shielding performance of the membrane material caused by uneven dispersion of the filler is avoided. At the same time, the mechanical properties of the membrane material are prevented from decreasing due to the addition of powder fillers, and the powder is fixed in the structural frame.
[0013] In a specific embodiment, the mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder is (10-15):(12-16):1.
[0014] By loading nano titanium dioxide, carbon black and chrome black powder in a certain proportion of activated carbon, the full shading film has a considerable shading rate, and the mechanical properties of the material are guaranteed, so that the aging resistance and weather resistance are significantly improved.
[0015] In a specific embodiment, the light reflection aid is zinc oxide having an oil absorption value of 20 g / 100 g to 30 g / 100 g.
[0016] The light reflecting agent and the light-shielding filler can cooperate with each other to enhance the light-shielding performance of the polypropylene composite material and improve its reflectivity; the nano zinc oxide and the light-shielding filler work together to have a balanced absorption of ultraviolet energy in each band, so that the ultraviolet absorption effect is the best and the transmittance of the ultraviolet band reaches the lowest point, thereby effectively improving the weather resistance and aging resistance of the highly weather-resistant light-shielding film.
[0017] The antioxidant is a hindered phenol antioxidant.
[0018] In a second aspect, the present application provides a method for preparing an aging-resistant and highly stable full-light-shielding film, which adopts the following technical solution: A method for preparing an aging-resistant and highly stable full-light-shielding film comprises the following steps: Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, and then a lubricant is added. After twin-screw extrusion granulation, a light-shielding filler, a light-reflecting auxiliary agent and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; The mixed material is put into a twin-screw extruder for melting and extrusion, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling.
[0019] In a specific embodiment, the melt processing temperature is 180-220°C and the screw speed is 25-35HZ.
[0020] In summary, this application has the following beneficial effects: 1. Through the cross-linking reaction of modified polyurethane and epoxy resin to provide a cross-linked skeleton, the epoxy resin exhibits excellent physical properties and chemical corrosion resistance on the above structural framework, forming the basis of a flexible and durable full-light-shielding film material. Then, by adding polybutylene terephthalate PBT, which belongs to the polyester series, the longer ester chain segment in the crystalline thermoplastic polyester resin can be deeply wound around the above structural framework, further improving the toughness and wear resistance of the overall material, and improving the structural strength, drape and durability of the full-light-shielding film. The light can be effectively blocked by the light-shielding filler, and the light-shielding effect is good. The mixed use of the light-shielding filler and the light-reflecting additive can give full play to the light-shielding and light-reflecting effects, avoid direct light exposure to the dark light-shielding layer and accelerate the aging of the dark light-shielding layer, and extend the overall service life of the full light-shielding film. The overall color deviation of the product made in this way is small, and the light-shielding effect of the product is uniform and consistent. It can be used to make full-light-shielding curtains, roller blinds, tents, sunshade cloths, etc., with a wide range of uses, reducing manufacturing costs and increasing the demand for high-quality products.
[0021] 2. Enhance the light-shielding performance of the composite material and improve its reflectivity; nano zinc oxide and light-shielding fillers work together to achieve balanced absorption of ultraviolet energy in each band, making the ultraviolet absorption effect the best and the transmittance of the ultraviolet band reaching the lowest point, thereby effectively improving the weather resistance and aging resistance of the highly weather-resistant light-shielding film. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments.
[0023] Some of the raw materials used in the preparation examples and embodiments: polyurethane TPU brand: 9370AU; PBT brand: 1100-211M; epoxy resin brand: E-44; activated carbon model: DQ-180; nano-silica brand: HOMBITEC RM200; carbon black model: T250; chrome black powder purchased from Foshan Shenghui New Material Technology Co., Ltd.; hindered phenol antioxidant model: BASF antioxidant 1098; zinc oxide brand: FZn90; lubricant model: SILIKELYSI-408.
[0024] The raw materials used in the examples and comparative examples that are not otherwise specified are all conventional products that can be purchased from the market.
[0025] Preparation of activated carbon supported nano-titanium dioxide Preparation Example 1 20 g of activated carbon was added to 100 mL of 2 mol / L ethanol solution of tetrabutyl titanate for mixed adsorption and allowed to stand for 2 hours to obtain a precursor; the precursor was dried at 65° C. in a ventilated environment, crushed and obtained, and then heated to 200° C. and kept warm for 3 hours, then heated to 650° C. and calcined in the absence of oxygen for 2 hours, and then cooled to room temperature to obtain the activated carbon-loaded nano-titanium dioxide. Example Example
[0026] A fully shading film with high stability and anti-aging properties comprises the following components calculated in parts by weight: 38 g of modified polyurethane TPU, 15 g of PBT, 15 g of epoxy resin, 8 g of lubricant, 16 g of shading filler, 3 g of light reflection aid, and 1.5 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide, carbon black, and chrome black powder, and the mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black, and chrome black powder is 15:12:1; the activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0027] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0028] A fully shading film with high stability and anti-aging properties comprises the following components calculated by weight: 50 g of modified polyurethane TPU, 10 g of PBT, 18 g of epoxy resin, 5 g of lubricant, 8 g of shading filler, 5 g of light reflection aid and 1 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder, and the mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder is 15:12:1; the activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0029] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0030] A fully shading film with high stability and anti-aging properties comprises the following components calculated in parts by weight: 45 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid and 1 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder, and the mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder is 15:12:1; the activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0031] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0032] A fully shading film with high stability and anti-aging properties comprises the following components calculated by weight: 45 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid and 1 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder, and the mass ratio of activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder is 15:12:5; activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0033] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0034] A fully shading film with high stability and aging resistance comprises the following components calculated by weight: 45 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid, and 1 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide, and the activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0035] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0036] A fully shading film with high stability and aging resistance comprises the following components calculated by weight: 45g of modified polyurethane TPU, 12g of PBT, 16g of epoxy resin, 8g of lubricant, 15g of shading filler, 5g of light reflection aid, and 1g of antioxidant; wherein the shading filler is carbon black.
[0037] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0038] A fully shading film with high stability and aging resistance comprises the following components calculated by weight: 45 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid, and 1 g of antioxidant; wherein the shading filler is chrome black powder.
[0039] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0040] A highly stable and aging-resistant full-light-shielding film comprises the following components calculated in parts by weight: 45 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of light-shielding filler, 5 g of light-reflecting auxiliary agent, and 1 g of antioxidant; wherein the light-shielding filler is activated carbon-loaded nano-titanium dioxide and carbon black, and the mass ratio of the activated carbon-loaded nano-titanium dioxide to the carbon black is 16:12; the activated carbon-loaded nano-titanium dioxide is prepared in Preparation Example 1.
[0041] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0042] A fully shading film with high stability and aging resistance comprises the following components calculated by weight: 45 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid, and 1 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide and chrome black powder, and the mass ratio of activated carbon-loaded nano-titanium dioxide to chrome black powder is 27:1; activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0043] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling. Example
[0044] A fully shading film with high stability and aging resistance comprises the following components calculated by weight: 45 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid, and 1 g of antioxidant; wherein the shading filler is carbon black and chrome black powder, and the mass ratio of carbon black to chrome black powder is 27:1; activated carbon-loaded nano titanium dioxide is prepared as in Preparation Example 1.
[0045] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling.
[0046] Comparative Example 1 A fully shading film with high stability and anti-aging properties comprises the following components calculated in parts by weight: 45 g of polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid, and 1 g of antioxidant; wherein the shading filler comprises activated carbon-loaded nano-titanium dioxide, carbon black, and chrome black powder, and the mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black, and chrome black powder is 15:12:1; the activated carbon-loaded nano-titanium dioxide is prepared according to Preparation Example 1.
[0047] Polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, and then a lubricant is added. After twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C. After cooling, the mixture is pelletized and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling.
[0048] Comparative Example 2 A fully shading film with high stability and anti-aging properties comprises the following components calculated by weight: 60 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 5 g of light reflection aid and 1 g of antioxidant.
[0049] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, and then a lubricant is added. After twin-screw extrusion granulation, a light reflecting agent and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C. After cooling, the mixture is pelletized and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and after cooling, a full light-shielding film is obtained.
[0050] Comparative Example 3 A fully shading film with high stability and anti-aging properties comprises the following components calculated by weight: 50 g of modified polyurethane TPU, 12 g of PBT, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler and 1 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder, and the mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder is 15:12:1; the activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0051] Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, granulated by twin-screw extrusion, and then a light-shielding filler and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling.
[0052] Comparative Example 4 A fully shading film with high stability and anti-aging properties comprises the following components calculated in parts by weight: 57 g of modified polyurethane TPU, 16 g of epoxy resin, 8 g of lubricant, 15 g of shading filler, 5 g of light reflection aid and 1 g of antioxidant; wherein the shading filler is activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder, and the mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder is 15:12:1; the activated carbon-loaded nano-titanium dioxide is prepared as in Preparation Example 1.
[0053] Modified polyurethane TPU and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, then a lubricant is added, and after twin-screw extrusion granulation, a light-shielding filler, a light-reflecting aid, and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; the mixture is put into a twin-screw extruder with a screw speed of 25 Hz and a melt extrusion temperature of 200°C, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling.
[0054] The aging-resistant and highly stable full-light-shielding films prepared in the embodiments and comparative examples; a. Tensile strength and elongation at break: Tested in accordance with the method specified in GB / T 13022-1991; 5 test points are taken for each sample, and the obtained data are averaged; b. Shading rate: Compound the high weather-resistant shading film to be tested with solid-color polyester fabric (weight 120g / m2), and then test the shading performance according to the light transmission "box method" described in AATCC-148-79; c. Aging resistance: The high weather-resistant light-shielding film to be tested is placed in a UV-ozone aging test chamber for testing, with the UV radiation intensity of 400μW / cm 2 , ozone concentration is 20ppm, temperature is 28℃, and the tensile strength is tested after continuous irradiation for 240h; 5 test sites are taken for each sample, and the obtained data are averaged; the tensile strength measured at this time is compared with the tensile strength before ultraviolet irradiation to obtain the performance retention rate; the comparison results are shown in Table 1 below: Table 1 Performance test results As can be seen from Table 1, the aging-resistant and highly stable full-light-shielding film obtained in the above embodiment has a high light-shielding rate, good long-term stability, good weather resistance, and is suitable for commercial promotion and use. Compared with Examples 5-10, it can be seen that the mechanical properties and aging resistance of the aging-resistant and highly stable full-light-shielding film prepared in Example 3 are better than those of Examples 5-10. It is analyzed that the activated carbon-loaded nano-titanium dioxide is matched with two light-shielding fillers. The activated carbon-loaded nano-titanium dioxide has the function of reflecting light, which can produce good reflection and scattering, and prevent light from passing through the composite material, so that the full-light-shielding film has certain mechanical properties, and the aging resistance and weather resistance are significantly improved. Under the premise of ensuring the light-shielding rate, the weather resistance is greatly improved.
[0055] By comparing Example 3 with Comparative Example 1, it can be seen that the mechanical properties and aging resistance of the aging-resistant and highly stable full-light-shielding film prepared in Example 3 are better than those in Comparative Example 1. Analysis shows that, through the cross-linking reaction of modified polyurethane and epoxy resin to provide a cross-linked skeleton, the epoxy resin exhibits excellent physical properties and chemical corrosion resistance on the above-mentioned structural framework, forming the basis of a flexible and durable full-light-shielding film material, improving the toughness and wear resistance of the overall material, and improving the structural strength, drape and durability of the full-light-shielding film.
[0056] By comparing Example 3 and Comparative Example 4, it can be seen that the mechanical properties and aging resistance of the aging-resistant and highly stable full-light-shielding film prepared in Example 3 are better than those in Comparative Example 4. It is analyzed that the cross-linking skeleton is provided by the cross-linking reaction of modified polyurethane and epoxy resin, and then the longer ester group segment in polybutylene terephthalate PBT is added, which can be deeply wrapped around the above-mentioned structural frame, thereby further improving the toughness and wear resistance of the overall material, and improving the structural strength, drape and durability of the full-light-shielding film. The light can be effectively blocked by the shading filler, and the shading effect is good.
[0057] By comparing Example 3 and Comparative Examples 2-3, it can be seen that the mechanical properties and aging resistance of the aging-resistant and highly stable full-light-shielding film prepared in Example 3 are better than those of Comparative Examples 2-3. Analysis shows that the light reflection aid and the light-shielding filler can cooperate with each other to enhance the light-shielding performance of the polypropylene composite material and improve its reflectivity; nano zinc oxide and the light-shielding filler work together to have a balanced absorption of ultraviolet energy in each band, so that the ultraviolet absorption effect is the best, and the transmittance of the ultraviolet band reaches a low point, thereby effectively improving the weather resistance and aging resistance of the highly weather-resistant light-shielding film.
[0058] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. An aging-resistant and highly stable full-light-shielding film, characterized in that: The invention comprises the following components calculated by weight: 38-50 parts of modified polyurethane TPU, 10-15 parts of PBT, 15-18 parts of epoxy resin, 5-8 parts of lubricant, 8-16 parts of light-shielding filler, 3-5 parts of light-reflecting auxiliary agent and 1-1.5 parts of antioxidant.
2. The aging-resistant and highly stable full-light-shielding film according to claim 1, characterized in that: The modified polyurethane TPU is an acrylic modified polyurethane TPU, and the preparation method comprises the following steps: mixing and reacting a diol with an isocyanate to obtain a prepolymer terminated with isocyanate groups at both ends; and then mixing and reacting with a hydroxyl-containing acrylate to obtain the acrylic modified polyurethane TPU.
3. The aging-resistant and highly stable full-light-shielding film according to claim 1, characterized in that: The light-shielding filler comprises activated carbon-loaded nano titanium dioxide, carbon black and chrome black powder.
4. The aging-resistant and highly stable full-light-shielding film according to claim 3, characterized in that: The preparation method of activated carbon-supported nano titanium dioxide comprises the following steps: mixing activated carbon and an ethanol solution of tetrabutyl titanate for adsorption, and standing for 1-2 hours to obtain a precursor; and drying and calcining the precursor to obtain the activated carbon-supported nano titanium dioxide.
5. The aging-resistant and highly stable full-light-shielding film according to claim 3, characterized in that: The mass ratio of the activated carbon-loaded nano-titanium dioxide, carbon black and chrome black powder is (10-15): (12-16):
1.
6. The aging-resistant and highly stable full-light-shielding film according to claim 1, characterized in that: The light reflection auxiliary agent is zinc oxide with an oil absorption value of 20g / 100g-30g / 100g.
7. The aging-resistant and highly stable full-light-shielding film according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant.
8. A method for preparing an aging-resistant and highly stable full-light-shielding film according to claims 1-7, characterized in that: Modified polyurethane TPU, PBT and epoxy resin are added in proportion in sequence, mixed at high speed in a high-speed mixer, and then a lubricant is added. After twin-screw extrusion granulation, a light-shielding filler, a light-reflecting auxiliary agent and an antioxidant are added and mixed at high speed for 20 minutes to obtain a mixture; The mixed material is put into a twin-screw extruder for melting and extrusion, pelletized after cooling, and dried to obtain prefabricated particles; the prefabricated particles are put into a casting machine for extrusion and casting, and a full light-shielding film is obtained after cooling.
9. The method for preparing an aging-resistant and highly stable full-light-shielding film according to claim 8, characterized in that: The melt processing temperature is 180-220°C and the screw speed is 25-35HZ.